2007
DOI: 10.1111/j.1464-5491.2006.02073.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gestational diabetes mellitus and the effect of weight on measures of insulin secretion and insulin resistance in third‐trimester pregnant rural women residing in the Central Region of Limpopo Province, South Africa

Abstract: The present study shows that there is a high prevalence of GIGT/GDM, with most women having IGT. The GIGT/GDM present in these women is characterized by increased insulin sensitivity accompanied by reduced pancreatic B-cell function. Additionally, heavier women appear to have increased first phase insulin secretion, suggesting the presence of insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
3
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 37 publications
6
51
3
1
Order By: Relevance
“…The current study, employing the revised WHO diagnostic criteria, gives an overall prevalence rate of 13.4% among these women with identified risk factors. A South African study, also using the same criteria, reported a prevalence rate of 8.8% among a group of 262 third trimester pregnant women 8. Our value is however much lower than reported among similarly selectively screened women in western India, where a rate of 21.6% was observed 9.…”
Section: Discussioncontrasting
confidence: 48%
“…The current study, employing the revised WHO diagnostic criteria, gives an overall prevalence rate of 13.4% among these women with identified risk factors. A South African study, also using the same criteria, reported a prevalence rate of 8.8% among a group of 262 third trimester pregnant women 8. Our value is however much lower than reported among similarly selectively screened women in western India, where a rate of 21.6% was observed 9.…”
Section: Discussioncontrasting
confidence: 48%
“…Mothers who develop gestational diabetes mellitus have an increased risk of developing type 2 diabetes mellitus, and infants born to mothers who have gestational diabetes mellitus are at an increased risk of adverse birth outcomes, including macrosomia and childhood obesity. 38-40 A reason for the low prevalence of gestational diabetes mellitus could be the low mean age (26.3 ± 5.4 years) of the women in this study, which is comparable with that of the women in a study by Mamabola et al 41 The highest proportion of women who developed gestational diabetes mellitus were categorised in the obesity group. This is in agreement with the findings of Mamabola et al, 41 who also reported that women who developed gestational diabetes mellitus were significantly heavier than those who did not.…”
Section: Discussionsupporting
confidence: 73%
“…(Mamabolo et al 2007). Although the prevalence of GDM highly depends on method and criteria used, pre-pregnancy BMI, a strong predictor of GDM in other studies, (Schneider et al 2012;Mamabolo et al 2007) was not associated with GDM-perhaps due to differences in dietary behavioral factors and balance between nutrient metabolism and degree of adipogenesis, as well as innate genetic predisposition. Age and firstfamily history of diabetes were associated with GDM as consistently reported elsewhere (Aberg et al 2002).…”
Section: Discussionmentioning
confidence: 99%